Differential Pulmonary Rehabilitation Outcomes in Patients With and Without COPD: ROLE OF GENDER. Issue 5 (September 2017) - Nguyen, Lam-Phuong; Beck, Emily; Cayetano, Katherine; Li, Chin-Shang; Hardin, Kimberly
Abstract : Purpose: Individuals with all forms of pulmonary disease are referred for pulmonary rehabilitation. This study examines pulmonary rehabilitation outcomes between individuals with chronic obstructive lung disease (COPD) and non-COPD disease and the impact of gender. Methods: This is a retrospective study at a tertiary center. The primary endpoint was the difference in 6-min walk test distance. Secondary measurements included treadmill and NuStep minutes; biceps curls and front arm raises load; quality of life measured by the St George's Respiratory Questionnaire; and University of California San Diego-Shortness of Breath Questionnaire (UCSD-SOBQ) scores. Results: Eighty patients were included: 38 men (23 COPD, 15 non-COPD) and 42 women (31 COPD, 11 non-COPD). There was a statistically significant improvement in 6-min walk test distances pre- to post–pulmonary rehabilitation for all participants, P = .0003. Although both the COPD and non-COPD groups demonstrated overall improvement ( P < .0004 and P = .02, respectively), subgroup analysis showed no statistically significant change in the non-COPD group when divided by gender. There was a significant statistical improvement in lower and upper extremity strength in all participants. Only women with COPD showed a statistically significant improvement with respect to overall quality of life as measured by St. George's Respiratory Questionnaire ( P = .01). Women showed significant improvement in their depression score, as well as a trend toward improvement in the University of California San Diego-Shortness of Breath Questionnaire, while only men with COPD showed any improvement in their sleep quality measured by the Pittsburgh Sleep Quality Index. Conclusions: Pulmonary rehabilitation results in different but improved outcomes regardless of gender or disease state. Abstract : Today, individuals with all forms of pulmonary disease are referred for pulmonary rehabilitation (PR). Our study examines PR outcomes between individuals with COPD and non-COPD disease and the impact of gender. Results demonstrated that PR is beneficial regardless of gender or disease state, although with different outcome parameters.